METALS IN HERBACEOUS PLANTS WITH DIFFERENT TYPES OF ADAPTIVE STRATEGIES - M. Sh. Sibgatullina; G. R. Valeeva (Юг России: экология, развитие)
Content of biophile elements and heavy metals in herbaceous plants of Tatarstan which belong to different types of adaptive strategies on Ramenskiy-Grime theory and to different ecological groups growing in different conditions of environments water regime was investigated in the article. It was statistically proved that plants with different types of adaptive strategies differ in the content of Zn. It was established that stress tolerators accumulate the studied elements in bigger quantity, than ruderals and competitors. Decrease of content of biophile elements and heavy metals in plants in the following line was revealed: mezophytes → xerophytes → mezohigrophytes.